Адаптация клеща Rhizoglyphus echinopus к новым кормовым субстратам - Барабанова, В.В. (Вестник зоологии, 1976)
Studies in the possibility of the Rh. echinopus digestive system adaptation to feeding on various food substrates, including those of animal origin, showed that, in spite of different attitude of Rh. echinopus to various kinds of food, its digestive system responds quickly to qualitative and quantitative changes in food composition by changes in activity of the corresponding group of enzymes. This, probably, is the reason of highly variable food of this species.